MOUNTAINOUS BROWN SOILS AND SEVERSOV PINE (FRITILLARIA SEWERZOWII REGEL.) IN MICROELEMENTS BIOGEOCHEMICAL MONITORING - Isomiddinov Zokirjon Jaloldinovich (Web of Journals Publishing, 2025)
This scientific article is aimed at studying the distribution and biological assimilation of microelements Fe, Mn, Zn, Mo, Co in mountain brown soils and the wild plant Fritillaria sewerzowii Regel. The average concentration of microelements in the soil and plant organs was determined and compared with the soil clarke values. The results showed moderately high Fe content and significant accumulation in the organs of the onion and roots. The concentration of Mn and Zn is high in the roots and seeds, and low in the leaves. Mo and Co are mainly found in the organs of the root and bulb, which affect the biological activity and medicinal properties of plants. It has been established that the distribution of microelements is closely related to the mechanical composition of the soil, the amount of humus, genetic horizons, and agroecological conditions. In addition, the coefficients of biological absorption of soil and plants were calculated. The results of this study will create a scientific basis for assessing the nutritional potential, biological assimilation mechanism, and medicinal value of the Seversov onion plant (Fritillaria sewerzowii Regel.) in mountain brown soils and will serve the development of ecological monitoring and agricultural practices in the future.
Keywords: Fritillaria sewerzowii, mountain brown soils, microelements, biological absorption coefficient, nutritional potential, medicinal plant, soil-plant relationship.